2019
DOI: 10.1021/acs.chemmater.9b00592
|View full text |Cite
|
Sign up to set email alerts
|

Controlling the Negative Thermal Expansion and Response to Pressure in ReO3-type Fluorides by the Deliberate Introduction of Excess Fluoride: Mg1–xZr1+xF6+2x, x = 0.15, 0.30, 0.40, and 0.50

Abstract: Cubic ReO 3 -type fluorides often display negative or very low thermal expansion. However, they also typically undergo phase transitions upon cooling and/or modest compression, which are undesirable from the perspective of potential applications. Density measurements and total scattering data for Mg 1−x Zr 1+x F 6+2x , x = 0.15, 0.30, 0.40, and 0.50, indicate that the introduction of excess fluoride into cubic MgZrF 6 is accompanied by the population of interstitial fluoride sites and the conversion of corner … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
34
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(41 citation statements)
references
References 58 publications
7
34
0
Order By: Relevance
“…119,123,125 There are also the recent reports of the fluoride rich ReO 3 -type compound, YbZrF 7 , 133 which displays NTE below room temperature and ZTE at 300 K, and the Mg 1x Zr 1+x F 6+2x compounds in which the degree of thermal expansion can be tuned by varying x. 134 ReO 3 -type oxyfluorides, with general formula MO x F y (M = Ti, 135 V, 136 Ta, 137 Nb, 135,137 Zr, 138 Mo 139 ) are also known, with the first example reported in the 1950's. 137 and MgTi 2 OF 8 .…”
Section: Inorganicsmentioning
confidence: 99%
“…119,123,125 There are also the recent reports of the fluoride rich ReO 3 -type compound, YbZrF 7 , 133 which displays NTE below room temperature and ZTE at 300 K, and the Mg 1x Zr 1+x F 6+2x compounds in which the degree of thermal expansion can be tuned by varying x. 134 ReO 3 -type oxyfluorides, with general formula MO x F y (M = Ti, 135 V, 136 Ta, 137 Nb, 135,137 Zr, 138 Mo 139 ) are also known, with the first example reported in the 1950's. 137 and MgTi 2 OF 8 .…”
Section: Inorganicsmentioning
confidence: 99%
“…These include (a) forming solid solutions by isovalent cation substitution to make Sc 1−x Y x F 3 , 2 Sc 1−x Al x F 3 , 3 Sc 1−x Ti x F 3 , 4 Sc 1−x Fe x F 3 , 5,6 Sc 1−x (Ga/Fe) x F 3 , 7 and Sc 1−x (Al/Fe) x F 3 ; 8 (b) preparing cation-ordered double ReO 3type materials such as CaZrF 6 , 9 other M II ZrF 6 's, 10,11 CaTiF 6 , 12 M II Nb IV F 6 11,13 and solid solutions based on these materials; 14,15 (c) including guests in the open A-sites of the ReO 3structure by redox insertion 16 or high-pressure gas treatment; 17 and (d) deliberately introducing excess fluoride by aliovalent cation substitution to make materials such as Sc 1−x Zr x F 3+δ , 18 YbZrF 7 , 19 Ti 1−x Zr x F 3+x , 20 and [Mg 1−x Zr x ]ZrF 6+2x . 21 Isovalent cation substitution and the creation of stoichiometric double ReO 3 -type materials often lead to compositions that undergo an undesirable structural phase transition from the cubic phase, which has interesting thermal expansion characteristics, to a lower symmetry or disordered material upon cooling or modest compression. However, our recent work on [Mg 1−x Zr x ]ZrF 6+2x 21 demonstrated that the introduction of excess fluoride by aliovalent cation substitution not only provides control of thermal expansion but also suppresses the undesirable cubic to rhombohedral phase transition that is seen upon cooling or compressing the parent composition MgZrF 6 .…”
Section: Introductionmentioning
confidence: 99%
“…21 Isovalent cation substitution and the creation of stoichiometric double ReO 3 -type materials often lead to compositions that undergo an undesirable structural phase transition from the cubic phase, which has interesting thermal expansion characteristics, to a lower symmetry or disordered material upon cooling or modest compression. However, our recent work on [Mg 1−x Zr x ]ZrF 6+2x 21 demonstrated that the introduction of excess fluoride by aliovalent cation substitution not only provides control of thermal expansion but also suppresses the undesirable cubic to rhombohedral phase transition that is seen upon cooling or compressing the parent composition MgZrF 6 . 11 This was attributed to changes in the local structure of the material, which inhibit the cooperative octahedral tilting associated with the cubic to rhombohedral transition.…”
Section: Introductionmentioning
confidence: 99%
“…Although most materials display positive thermal expansion (PTE) due to the inherent anharmonicity of bond potentials, some display the anomalous properties of negative thermal expansion (NTE) or near-zero thermal expansion (ZTE). In principle, NTE materials can be used to compensate for the PTE of a matrix resulting in a controlled thermal expansion composite. , NTE in open framework materials, , such as metal oxides, ,, metal fluorides/oxyfluorides, cyanides, and metal–organic frameworks (MOFs), typically arises from the presence of low frequency vibrational modes that soften on volume reduction. , Strategies for controlling NTE in a given framework, such as the formation of solid solutions or the insertion of guest molecules, , can be thought of as methods for modifying the vibrational modes and their response to volume change.…”
Section: Introductionmentioning
confidence: 99%
“…Construction of countless MOF topologies, using different metals (or metal clusters) and organic ligands, is possible . The preparation of solid solutions incorporating different ligands or metal clusters in a single-phase material enables fine-tuning of material properties, including thermal expansion. , Although NTE has been reported in a number of MOFs, , studies leveraging the modular buildup and controlled exchangeability of building blocks, or the preparation of solid solutions, to manipulate thermal behavior are scarce. , To our knowledge, there is no experimental evidence of tunable thermal expansion from negative to positive via the formation of MOF solid solutions in the peer-reviewed scientific literature, although there have been reports where the magnitude of thermal expansion has been tuned by incorporating guest molecules, isovalent metals, and structural defects. , …”
Section: Introductionmentioning
confidence: 99%